2007
DOI: 10.1271/bbb.60351
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Bisphenol A and Related Compounds bySphingomonassp. Strain BP-7 Isolated from Seawater

Abstract: A bacterium capable of assimilating 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), strain BP-7, was isolated from offshore seawater samples on a medium containing bisphenol A as sole source of carbon and energy, and identified as Sphingomonas sp. strain BP-7. Other strains, Pseudomonas sp. strain BP-14, Pseudomonas sp. strain BP-15, and strain no. 24A, were also isolated from bisphenol A-enrichment culture of the seawater. These strains did not degrade bisphenol A, but accelerated the degradation of bisphenol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 18 publications
4
39
0
1
Order By: Relevance
“…Considering that most of the BPA-degrading bacteria previously isolated also belong to the family Sphingomonadaceae (20,31,32), this family seems to play a major role in the depletion of various bisphenols in the aquatic environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that most of the BPA-degrading bacteria previously isolated also belong to the family Sphingomonadaceae (20,31,32), this family seems to play a major role in the depletion of various bisphenols in the aquatic environment.…”
Section: Discussionmentioning
confidence: 99%
“…BPA has been identified as an endocrine-disrupting chemical that may cause adverse effects on human health and wildlife (7,19,39). A number of BPA-degrading bacteria have been isolated from enrichments of sludge from wastewater treatment plants (20,25), aquatic environments (23,24,31), soil (30,33), and samples of compost leachate (43). Spivack et al (36) revealed that BPA is biodegraded via major and minor pathways, both involving the oxidative skeletal rearrangement of an unactivated aliphatic methyl group in the BPA molecule.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It completely degraded 115 mg/l BPA at the sixth hour and showed a little higher degradation efficiency than that of the three Sphingomonas sp. strains SO11, SO1a, and SO4a isolated by Matsumura et al (2009) that completely degraded 115 mg/l BPA within 15 h. Sakai et al (2007) reported the first seawater BPA-degrading isolate of Sphingomonas sp. strain BP-7.…”
Section: Bpa Degradation By Gram-negative Bacteriamentioning
confidence: 99%
“…-199 -Recent studies have reported that Sphingomonas sp. degrade dioxin, nonylphenol, polycyclic aromatic hydrocarbon (PAH), and other persistent substances (Wilkes et al, 1996;Tanghe et al, 1999;Shi et al, 2001;Sakai et al, 2007). We expect this study to promote the research on the dynamics of the bacteria involved in the degradation of persistent substances in situ.…”
Section: Quantification Of Microcystin-degrading Bacteria By Real-timmentioning
confidence: 88%